Association between expression of Carboxypeptidase 4 and stem cell markers and their clinical significance in liver cancer development - Sun, Lichao (J Cancer, 2017)
The development of liver cancer would undergo a sequential progression from chronic inflammatory liver disease, cirrhosis to neoplasia. During these pathophysiological changes, abnormal liver microenvironment might induce the hepatocytes to die, abnormally proliferate and initiate cancer stem cells. Metallocarboxypeptidases (MCPs) involved in multiple biological functions including inflammation, fibrosis and stem cell niche formation. This study aimed to evaluate the expression of carboxypeptidase 4 (CPA4) in hepatitis, liver cirrhosis and liver cancer tissues, and revealed its clinical significance in liver cancer progression. We firstly found that the CPA4 levels in tissues were significantly higher in liver cancer patients than those in other three groups. Then, elevated levels of CPA4 was observed in 57/100 (57%) liver cancer samples, and significantly correlated with Grade and Stage. We also identified a significant positive correlation between aberrant elevation of CPA4 and overexpression of stem cell markers including CD90, AFP and CD34 with follow-up data (n=100). Further Kaplan-Meier analysis confirmed that high levels of CPA4 and CD90 were significant predictors of poor overall survival. Multivariate Cox regression model showed that CPA4 was an independent prognostic factor for patients with liver cancer. This study demonstrated for the first time that high CPA4 expression was closely correlated with hepatocarcinogenesis, and might be used as an independent poor prognostic factor in liver cancer.